2018
DOI: 10.2151/jmsj.2018-031
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Sea Surface Temperature and Rainfall in the Philippines during the Asian Summer Monsoon

Abstract: We offer a new perspective on a relationship between sea surface temperature (SST) over the windward region of the Philippines and rainfall in the western Philippines during the Asian summer monsoon season, which has been known as the negative correlation, using observational daily SST, rainfall, and atmospheric circulation datasets. This study focuses on the local SST effect rather than the remote effect. A warmer local SST results in greater rainfall over the western Philippines under similar monsoon westerl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Recent studies (Wang et al, 2005;Rajeevan et al, 2012;Chaudhari et al, 2013Chaudhari et al, , 2016Weller et al, 2016;Feng et al, 2018) have shown that the simulation of the ISM can be improved with the exact representation of the SST-precipitation relationship. SST modulates the meteorological factors that influence the formation and evolution of different kinds of precipitating systems over tropical oceans (Gadgil et al, 1984;Schumacher and Houze, 2003;Takayabu et al, 2010;Oueslati and Bellon, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies (Wang et al, 2005;Rajeevan et al, 2012;Chaudhari et al, 2013Chaudhari et al, , 2016Weller et al, 2016;Feng et al, 2018) have shown that the simulation of the ISM can be improved with the exact representation of the SST-precipitation relationship. SST modulates the meteorological factors that influence the formation and evolution of different kinds of precipitating systems over tropical oceans (Gadgil et al, 1984;Schumacher and Houze, 2003;Takayabu et al, 2010;Oueslati and Bellon, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…However, during JJA, climate variables with low correlation with SST have better correlation with observation. This implies that SST has a more direct statistical relationship with rainfall, for example, during DJF than JJA where the Asian summer monsoon has a direct effect (Ueda, 2005; Dado and Takahashi, 2017; Takahashi and Dado, 2018). Also, temperature, rainfall, and wind speed are adequately simulated by models over regions of SWM influence (i.e., WEST‐basin) where SST seasonal variability is captured well.…”
Section: Discussionmentioning
confidence: 99%
“…During JJA (Figure 9), the weak negative correlation between model SST and RegCM precipitation is different from the weak positive correlation found between model SST and GCMs. This implies that weak correlation and difference in sign are associated with other factors, such as SWM, the dominant climate driver during this season (Ueda, 2005; Dado and Takahashi, 2017; Takahashi and Dado, 2018). While downscaled simulations give better simulation of monsoon‐related seasonal contrasts, RegCM simulations are still affected by poor representation from GCM simulations, which provide the boundary conditions to RegCM.…”
Section: Potential Influence Of Sst Representation In Cordex‐sea Simu...mentioning
confidence: 99%
See 1 more Smart Citation
“…In turn, the SAT warming induces an increase in precipitation and a decrease in R ( s / p ) when the environmental SAT condition is close to the threshold value between snowfall and rainfall. Although monthly and seasonal observational data analyses indicated that SST had a weak impact on precipitation, some studies have suggested a positive contribution of SST to precipitation on intra‐seasonal time‐scales even under vigorous air‐sea interaction environments (Takahashi and Idenaga, 2013; Takahashi and Dado, 2018). Nevertheless, quantitative evaluations are ongoing.…”
Section: Discussionmentioning
confidence: 99%